Letter - Lizaso, Jose I. de
012a-0049-001 J. I. de Lizaso Delegate of the Basque Government Private Address 75 Gloucester Terrace Hyde Park London W.2 Tel. Paddington 5754 7th September,1938. Sir Walter Citrine, K.B.E., Trades Union Congress, BLACKPOOL. Dear Sir Walter, This is to introduce my good friend, Dr. Batista i Roca, London Delegate of the Government of Catalonia. Dr. Roca is anxious to communicate to you personally some important and confidential information regarding the present position in Spain, which both he and I feel will be of interest to you and your colleagues at the Conference. I should, therefore, appreciate it very much if you could spare him a few minutes of your valuable time. I am looking forward to seeing you myself in the early future. Yours sincerely, Jose I de Lizaso 292/946/12a/49